Uji Antikanker Ekstrak Metanol Jamur Yang Diisolasi Dari Tanah Di Cilacap Terhadap Sel Kanker MCF-7 Secara In Vitro - Wulan, Nina Sri; , Azis Saifudin, Ph.D., Apt (2017)
Soil is the basic ecosystem of all living organisms like microbes, one of them is fungus. Cultured soil microbes have been an incredibly productive source of natural drugs, such as doxorubicin, bleomycin, and mitomycin, so research which uses soil microbes is interesting to be done. The purpose of this study was to find out the anticancer effects of fungal isolates from forest land, fields, mountains, river banks, and poultry against MCF-7 cells. Fungal isolates were collected from soil screening which was done by soil suspension diluting from five different ecosystems using sterile saline solution until the concentration was 10-3, then planted on Czapex dox which was added with streptomycin, tetracycline, and yeast extract. Fungus were extracted using maceration method by soaking soil fungal isolates and fungal growth media. Each of the methanol extract of fungi isolates had concentration of 500; 250; 125; 62,5; and 31,25 µg/mL were tested by cytotoxic effect to MCF-7 cells using the MTT assay method. The result of cytotoxic test showed that the methanol extract of soil fungi isolates from five ecosystems could increase the number of living cell along with increase of the oncentration. Therefore it can be conclude that methanol extract of fungal isolates have no anticancer effect to MCF-7 cells.